Perlindungan Hukum Terhadap Anak Dari Perkawinan Beda Agama Dalam Memeluk Agama Dari Prespektif Hukum Islam - Himatul Ulya; Muhammad Faiz; Putri Umala; Muhammad Rian; Muhammad Lukman (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2024)
When two people, a woman, a man, have different beliefs, marry while practicing their respective religions, it is known as an interfaith marriage. However, interfaith unity raises unique problems, especially those related to children's rights. Marriage results in the birth of a child. In essence, sons or daughters who have offspring from a marriage bond must receive protection from laws in the social and state environment. This journal uses empirical or sociological research methods to find out how society and the law respond to interfaith marriages and the religious choices made by their descendants. Primary and secondary data regarding child safety and religious freedom—namely, that parents have no right to force their children to convert to their religion—were collected from legal materials found in books, journals, and online sources. That parents who have different beliefs are prohibited from forcing their children to practice their religion, especially if there are differences of opinion that have a negative impact on the children themselves. So, as parents, we must care for and advise with high dedication to our sons and daughters about religion and set a good example for them, and the state must defend the rights of children regardless of the child's legitimacy, religious beliefs, physical and mental health, or position. in a social environment.